Effect of mental illness stigma upon the quality of life among families with schizophrenic patients in Mental Health Centre, Sulaimaniyah, Iraq: Mental illness stigma upon the quality of life among families with schizophrenic patients - Mohammed Abdulkarim, Araz (Zanco Journal of Medical Sciences (ZJMS), 2025)
Background and objective: Family caregivers of members with schizophrenia are subjected to stigmatization that significantly affects the quality of life. And causes delays in caregiving and treatment seeking for schizophrenic patients. The objective is to assess the stigma of mental illness and QoL levels and to determine its association among family caregivers of schizophrenic patients. Methods: A quantitative cross-sectional study was performed on 100 family caregivers with schizophrenia in 100 patients selected at the Mental Health Center, General Teaching Hospital in Sulaimaniyah, Iraq, from December 2022 to February 2023. A questionnaire used for data collection by interviewing the caregivers was composed of three parts; socio-demographic characteristics of family caregivers and patients, the stigma of mental illness scale, and QoL-BREF. Results: Most family caregivers of patients with schizophrenia were males (72%) and siblings (49%). Moderate prevalence of stigma (78%) and low level of life (91%) were observed among caregivers. The likelihood ratio test results indicated that stigma was significantly associated with QoL (LR=4.912, P <0.05). The multinomial logistic regression model analysis showed that family caregivers with a high level of stigma were significantly four times lower QoL (P <0.05, odds ratio=4.43). Conclusion: Family caregivers experienced a moderate level of stigma and low QoL that reflects a failure to use practical approaches to prompt and satisfy their needs in the community.